PENINGKATAN KEMAMPUAN MENULIS TEKS NARRATIVE DENGAN METODE COOPERATIVE LEARNING SISWA KELAS XI IPA 5 SMAN I KAWEDANAN PADA SEMESTER GANJIL TAHUN PELAJARAN 2014/2015 - Suaidah, Masning (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
Writing is a productive skill since the students have to create a composition in form of sentence, paragraph, and text. The students need to develop grammatical order, coherence and unity in sentence. But in fact, there are many students who have difficulty in writing. It is because of their low writing knowledge and the bored learning methode during in class. The research method used is class action research. Population of this study are 32 students of XI IPA 5 grade SMAN 1 Kawedanan. Sampling technique in this study is purposive sampling. The independent variables are Cooperative Learning Methode and the dependent variable is narrative text writing skill. The result of this research is from 32 students there are 30 students or 93,75% who show the increasing in class activity and learning result. It can be concluded that Cooperative Learning Methode can increase narrative text writing skill of XI IPA 5 SMAN 1 Kawedanan students.Key Words: Cooperative learning methode, narrative text writing skill.